Analysis of Strategies for Reducing Maternal Mortality Rates (MMR) in Developing Countries: A Meta-Analysis - Mirza, Muhammad Syauqi; Ngurah Made Surya Deva W; Cynthia Monica (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
Introduction: Maternal mortality rate (MMR) remains a significant global health problem, especially in developing countries. This study aims to analyze MMR reduction strategies that have been implemented in developing countries through meta-analysis. Methods: This research uses a meta-analysis design. A literature search was conducted on PubMed, Scopus, and Web of Science databases to identify observational and interventional studies that reported MMR reduction strategies and outcomes in developing countries from 2018 to 2024. Extracted data included study characteristics, intervention strategies, and effect sizes (odds ratio, risk ratio, or mean difference). Meta-analysis was performed using a random effects model. Results: A total of 35 studies involving 1,254,387 participants met the inclusion criteria. The most commonly used strategies were increasing access and quality of antenatal care (6 studies), increasing access and quality of delivery services (6 studies), and increasing access and quality of postnatal care (7 studies). Meta-analysis showed that all these strategies significantly reduced MMR (OR = 0.65, 95% CI: 0.58-0.73; RR = 0.72, 95% CI: 0.65-0.80; MD = -15.8, 95% CI: -20.3 to - 11.3). Conclusion: Increasing access and quality of antenatal, delivery and postpartum services is an effective strategy in reducing MMR in developing countries. Implementing this strategy in a comprehensive and integrated manner is very important to achieve sustainable development goals in reducing MMR.